Implementasi Model Discovery LearningDalam Meningkatkan Proses Pembelajaran Tematik Terpadu Kelas IV Sekolah Dasar - Dwita, Putri Syafna; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This research is motivated by integrated thematic learning that has not been well implemented, still in the process of being perfected. The purpose of this study, to improve the integrated thematic learning process using the Discovery Learning model. This type of research is classroom action research using qualitative and quantitative approaches. This research was conducted in the second semester of the 2019/2020 school year at SDN 22 Ujung Gurun Padang City. The results showed an increase in: (1) the learning plan that is cycle I gained a percentage of 81.25% (Good), cycle II obtained a percentage of 96.87% (Very Good). (2) the aspect of the first cycle teachers obtained a percentage of 86.94% (Good), the second cycle obtained a percentage of 96.875% (Very Good). (3) Aspects of students in cycle I obtained a percentage of 86.94% (Good), cycle II obtained a percentage of 96.875% (Very Good). (4) Knowledge and skill aspects of cycle I with an average of 81.07 increased in cycle II with an average of 88.19. It can be concluded that the Discovery Learning model can improve the integrated thematic learning process in Elementary Schools.